Pengaruh Pencemaran Limbah Grey Water Terhadap Sifat Tanah Lempung di Kerobokan - I Gede Ngurah Arya Yudistira; Aribudiman, I Nyoman; Ardana, Made Dodiek Wirya; Parwita, Dewa Ngakan Putu Ananda; Palguna, I Made Bagus Arya (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2026)
This study analyzes the effect of grey water by permanganate content on the physical, mechanical, and bearing capacity properties of clay soil in Kerobokan, which is known for its high plasticity and significant swelling-shrinkage potential. The methodology involved laboratory testing on three soil samples, 1 control sample and 2 samples with different grey water content. The lab test includes water content testing, Spesific Gravity, Sieve analysis, Atterberg limits, standard Proctor compaction, unconfined compressive strength, and consolidation tests. The results indicate that the soil is classified as high-plasticity inorganic clay (CH) with an average water content of 47.32%. After exposure to elevated permanganate values, the soil exhibited a 3.03% decrease in specific gravity, increases in liquid limit and plastic limit of 4.96% and 9.58%, respectively, and an 11.71% reduction in unconfined compressive strength. The soil bearing capacity decreased by 2.88% due to the influence of the grey water contaminant. These findings confirm that grey water contamination, as represented by the permanganate value, affects the physical and mechanical characteristics of clay soil as well as its bearing capacity, which is an important consideration in building design and construction planning in the Kerobokan area.